Fibre reinforcement – the key to sustainable reinforced concrete structures - Nakov, Darko; Ejupi, Hatim; Markovski, Goran; Arangjelovski, Toni (Slovenian National Building and Civil Engineering Institute (ZAG), 2020)
One of the main reasons for strengthening, repair or even demolishing of concrete structures is the appearance of large deflections or cracks developed in the service life of the structures, caused by many different reasons. On the other hand, sustainability of concrete structures can be achieved if we avoid these actions by design of more durable structures. The addition of fibres to concrete is well known measure that can help in achieving this goal, proven by now on many short term tests. Since there is a scarcity of long-term tests dealing with fibre reinforced concrete, to find out the influence of different types of fibre reinforcement on the long-term deflections and long-term cracks of concrete structures, an experiment was carried out at the Faculty of Civil Engineering–Skopje. The experiment consists of 12 full scale reinforced concrete beams, all manufactured with concrete class C30/37, but reinforced with different types (steel, macro and micro polypropylene fibres and their combination) and amount of fibres (0, 0.38%, 0.39% and 0.76% from the volume) and additional longitudinal and transverse reinforcement. The results from the long-term tests showed up that even small amount of added fibre reinforcement have big influence on both deflections and cracks, thus ensuring more durable structures and reducing the costs for their possible repair or strengthening in future.
Keywords: fibre reinforcement; sustainability; experiment; long-term deflections; long-term cracks